Instalasi Perpipaan Air Bersih Masjid Al-Ikhwan Rancagong Legok Tangerang - Arnas, Yenni; Wildan, Muh; Ismail, KGS; Kurniawati, Zulina; Kurnianto, Benny (Politeknik Penerbangan Indonesia Curug, 2021)
Water is essential for life, but not all people can access tap water. In fact, many people use ground water, which is not measured its purity, to supply household, places of worship, public facilities, private offices, government offices, and etc. This problem was also observed on Al-Ikhwan Mosque building Jl. Masjid RT 01 RW 08 Rancagong Village, Legok District, Tangerang Regency, Banten Province. In addition, in this place the water installation was not available. Therefore, it was feasible to carry out community service activities in that location regarding to clean water supply and installation. The method of this project were (1) drilling to make wells as clean water supply, (2) Calculating the need for clean water as the basis in determining the capacity and the type of water pump, (3) building water storage (equipped with a floating sensor as a control media turn the pump on or off automatically), and (4) piping to support distribution system of clean water from well to tap. This method was expected to meet Indonesian National Standard of clean water installation system. This project was supported by lecturers / instructors as their responsibility to practice Tridharma of higher education. Cadets/students was also involved in this project so they can demonstrate their knowledge about standard of building facilities in society.